2022
DOI: 10.1186/s12888-022-03712-w
|View full text |Cite
|
Sign up to set email alerts
|

Is age of self-harm onset associated with increased frequency of non-suicidal self-injury and suicide attempts in adolescent outpatients?

Abstract: Background Self-harm in adolescents is an increasing public health concern and an important risk factor for suicide. We aimed to examine how age of self-harm onset in adolescents was associated with frequency of subsequent suicidal and non-suicidal self-harm (NSSI) episodes, and how age of onset and duration of self-harm may influence the frequency of self-harm. Methods Data from 103 adolescents with recurrent self-harm recruited from child and ado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
2
14
0
1
Order By: Relevance
“…In fact, higher BPD symptom severity has predicted superior outcomes in DBT ( Seow et al, 2020 ) and skills-focused therapies might be more suitable for patients with personality disorders than depressed individuals. BPD severity was not directly examined in this study, but frequency and duration of DSH behaviour has been found to be associated with higher degrees of borderline pathology ( Brager-Larsen et al, 2022 ). Of note, the DBT-A group had a higher mean frequency of DSH as well as BPD traits at baseline.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, higher BPD symptom severity has predicted superior outcomes in DBT ( Seow et al, 2020 ) and skills-focused therapies might be more suitable for patients with personality disorders than depressed individuals. BPD severity was not directly examined in this study, but frequency and duration of DSH behaviour has been found to be associated with higher degrees of borderline pathology ( Brager-Larsen et al, 2022 ). Of note, the DBT-A group had a higher mean frequency of DSH as well as BPD traits at baseline.…”
Section: Discussionmentioning
confidence: 97%
“…In the short term, DSH reduces negative affect ( Rodriguez-Blanco et al, 2018 ), however reinforces long-term dysregulated affect ( Nock & Prinstein, 2004 ). Earlier age of onset and longer history of DSH predicted higher DSH frequency and increased risk of suicide attempts in treatment-seeking adolescents ( Brager-Larsen et al, 2022 ). Additionally, repeated DSH has been related to increased inclination to act on suicidal urges through pain habituation and diminished fear of death ( Hamza et al, 2012 ; Van Orden et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, there is evidence that age of onset of BPD symptoms predicts developmental outcomes. A recent study demonstrated that earlier age of self-harm onset and longer duration of self-harm were both associated with increased frequency of subsequent periods of self-harm and risk of first suicide attempt ( 44 ). Lower age of onset was also associated with more repeated suicide attempts.…”
Section: Seven Arguments Why Early Diagnosis and Treatment Of Pd Is J...mentioning
confidence: 99%
“…Hal ini membuktikan bahwa pada fase tersebut, mahasiswa berisiko untuk melakukan perilaku berbahaya seperi self-harm. Adanya data mengenai usia awal dan waktu terakhir melakukan self-harm sangat penting untuk mengetahui risiko pengulangan self-harm dan risiko bunuh diri (Barger-Larsen, Zeiner, Klungsoyr, & Mehlum, 2022).…”
Section: Self-harmunclassified